Rancang Bangun Sistem Online Shop Berbasis Website Untuk Meningkatkan Pendapatan di Toko Tanjung (Design and Build a Website-Based Online Shop System to Increase Revenue at Tanjung Stores) - Sri Mulyati (Universitas Muhammadiyah Tangerang, 2026)
Abstract The development of digital technology has encouraged many business sectors to switch to online platforms, including in the field of trade. Tanjung’s market, as a retail business, still relies on a conventional sales system that limits reach. This study aims to design and build a website-based online shop system to increase revenue and expand Tanjung's market. The analysis was carried out using the PIECES method to evaluate aspects of performance, information, economy, control, efficiency, and service in the existing system, as well as the design stage using UML (Unified Modelling Language). Meanwhile, the system development method applies the AGILE approach which allows the development process to run iteratively and flexibly according to user needs. Data were collected through observation, interviews, and literature studies. By implementing a website-based online shop system, it is hoped that Toko Tanjung can expand customer reach, as well as increase customer satisfaction through more modern and integrated transaction facilities. Keywords: Platform Online, Usaha Retail, Online Shop, Website, PIECES, UML,